Validation of the French version of the Multiple Sclerosis Intimacy and Sexuality Questionnaire 15 Tools which help nurse for assessing the effect of perceived multiple sclerosis symptoms on sexual activity and satisfaction - Sandrine Lefebvre; Marion Houot; Daniel Delgadillo; Marie Dominique Cantal Dupart; Dominique Varin; Caroline Papeix; Mathilde Sevin; Julie Bourmaleau; Florence Laigle‐Donadey; Ljiljana Jovic (Wiley, 2023)
Abstract Aim To validate a French version of the Multiple Sclerosis Intimacy and Sexuality Questionnaire 15 which examines patients' perception of the effect of multiple sclerosis symptoms on their sexual activity. Methods After completing a translation/re‐translation process to ensure linguistic and content validity, the Multiple Sclerosis Intimacy and Sexuality Questionnaire 15 French (MSISQ‐15Fr) was completed by patients with multiple sclerosis. The validity of the construction, reliability, stability and reproducibility of the translation was evaluated. Explanatory mixed observational study Validation of a French assessment tool for sexual disorders (borrowed theoretical framework): the Multiple Sclerosis Intimacy and Sexuality Questionnaire 15 (MSISQ 15) Results The normed χ2 was 1.21, the root mean square error of approximation was 0.046 [0.00; 0.07], the comparative fit index was 0.974, and the standardized root mean square was 0.065. The calculated Cronbach's coefficients indicated strong internal coherence, and the intraclass correlation coefficient was satisfactory at 0.9. Translations of the Multiple Sclerosis Intimacy and Sexuality Questionnaire 15 (MSISQ‐15) have already been validated in five languages. This French version is valid, stable and reproducible. It provides French‐speaking nurses an accessible and appropriate tool that will enable them to play an active role in the sexual health strategy recommended by the World Health Organization.